2018
DOI: 10.1177/1076029618764847
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Thrombin Generation Are Associated With Long-Term Clinical Outcome in Patients With ST-Segment Elevation Myocardial Infarction

Abstract: Hypercoagulability in ST-segment elevation myocardial infarction (STEMI) as related to long-term clinical outcome is not clarified. We aimed to investigate whether prothrombin fragment 1+2 (F1+2), d-dimer, and endogenous thrombin potential (ETP) measured in the acute phase of STEMI were associated with outcome. Blood samples were drawn median 24 hours after symptom onset in 987 patients with STEMI. Median follow-up time was 4.6 years. Primary outcome was a composite of all-cause mortality, reinfarction, stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…A "two-hit hypothesis", where both an inflammatory stimulus and activated platelets are required for NETosis in STEMI could explain the lack of association between the NETs-specific components and hypercoagulability markers peripherally 16 . We have previously shown that a prothrombotic state was predictive of death in this population, even after adjusting for the administration of prehospital thrombolysis 27 . Although fewer endpoints were recorded among patients receiving thrombolysis, the risk of death conferred by higher dsDNA levels was relatively unchanged when adjusting for both thrombolysis and D-dimer levels.…”
Section: Discussionmentioning
confidence: 84%
“…A "two-hit hypothesis", where both an inflammatory stimulus and activated platelets are required for NETosis in STEMI could explain the lack of association between the NETs-specific components and hypercoagulability markers peripherally 16 . We have previously shown that a prothrombotic state was predictive of death in this population, even after adjusting for the administration of prehospital thrombolysis 27 . Although fewer endpoints were recorded among patients receiving thrombolysis, the risk of death conferred by higher dsDNA levels was relatively unchanged when adjusting for both thrombolysis and D-dimer levels.…”
Section: Discussionmentioning
confidence: 84%
“…These eligible studies were published between 1999 and 2020. Four studies 8,9,17,24 were retrospective, and the others were prospective studies. The sample sizes of the included studies ranged from 165 to 8565, with a total of 25 600 patients with CAD.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Nine studies 8,9,16,18,20,21,[23][24][25] reported the association between D-dimer level and all-cause mortality. As shown in Figure 2, no significant heterogeneity was observed across these studies (I 2 ¼ 39.1%; P ¼ .107).…”
Section: All-cause Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several prospective studies have found low ETP/peak thrombin in the acute phase of CVD to be associated with outcome. Gremmel et al found low levels of peak thrombin to be associated incident AMI, stroke, TIA, or CVD death in patients having gone through angioplasty due to peripheral artery disease 15 ; Hansen et al found low ETP in the acute phase of ST-elevation myocardial infarction to be associated with a composite outcome 16 and Christersson et al found low acute-phase ETP in patients with AMI to be associated with stroke of any type (but not AMI). 17 In the former two studies, consumption of coagulation factors was again the proposed explanation.…”
Section: Discussionmentioning
confidence: 99%